47-3n=-23

Simple and best practice solution for 47-3n=-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 47-3n=-23 equation:


Simplifying
47 + -3n = -23

Solving
47 + -3n = -23

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-47' to each side of the equation.
47 + -47 + -3n = -23 + -47

Combine like terms: 47 + -47 = 0
0 + -3n = -23 + -47
-3n = -23 + -47

Combine like terms: -23 + -47 = -70
-3n = -70

Divide each side by '-3'.
n = 23.33333333

Simplifying
n = 23.33333333

See similar equations:

| Q-q+q+q=18 | | 5x=-3x-32 | | -3(r-6)=-9 | | 8x+4y=188 | | 6(x-9)-4(x+8)=1 | | 5log(x-5)=12 | | -4m+6=-8 | | -13n-(-2n)-(-15n)+-17n-(-10n)-10=5 | | 2y+4=y+7 | | 3x+3(1-x)=-17 | | 3x-2=5x-2 | | 84=6(m+7) | | (2x-1)+3(3x-5)=-2(2x+1) | | 10y+7=17 | | -x=-2x-1 | | 4q-3q+2q-1=11 | | 6x=2x+105 | | 0.5p+4.1=5.7-0.3p | | F=-2575+35x | | 4x-3=-5x-21 | | 30=2t-17t | | j+2=14 | | 15c=5 | | 2x+105=6x | | N+2n=57 | | -X+3(3)=12 | | -5x+10=-14-x | | 356b+56=-832 | | -17s+13s-8=-12 | | 2y-2y+y=17 | | 3x+1.5=6 | | 54=m(m-3) |

Equations solver categories